2017
DOI: 10.15244/pjoes/64655
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Toxicity Analysis and Reduction of Ceramsite Synthesis from Industrial Coal Gasification Coarse Cinder Waste

Abstract: Coal gasification coarse cinder (CGCC) is the main waste in the coal gasification industry, containing low calorific value but high heavy metal residuals. To achieve environmental toxicity stabilization and waste recycling, we developed a manufacturing method of multiple-functional ceramsite from CGCC by pelletizing and sintering. By altering key parameters during the manufacturing process (including CGCC content, sintering temperature, and time), the physical properties and leaching toxicity of ceramsite were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The white areas were feasible regions which could produce ceramsite adsorbents with acceptable fluoride removal ratio and ceramsite strength; 5.0 N is the minimum mechanical strength of qualified ceramsite (GB/T 17431.1–2010). The lower and upper bounds of ceramsite strength were 8.0 and 12.0 N respectively, except for the proportion of corn starch fixed at 0.2 (6.0–8.0 N), similar to that of industrial coal gasification coarse cinder ceramsite (3.2–24.0 N) . The lower and upper bounds of fluoride removal ratio were fixed at 80.0 and 92.0% respectively.…”
Section: Resultsmentioning
confidence: 78%
“…The white areas were feasible regions which could produce ceramsite adsorbents with acceptable fluoride removal ratio and ceramsite strength; 5.0 N is the minimum mechanical strength of qualified ceramsite (GB/T 17431.1–2010). The lower and upper bounds of ceramsite strength were 8.0 and 12.0 N respectively, except for the proportion of corn starch fixed at 0.2 (6.0–8.0 N), similar to that of industrial coal gasification coarse cinder ceramsite (3.2–24.0 N) . The lower and upper bounds of fluoride removal ratio were fixed at 80.0 and 92.0% respectively.…”
Section: Resultsmentioning
confidence: 78%
“…This suggests that the increase in the content of coarse slag reduces water absorption in the ceramsite. When these results were compared to those of sintered ceramsites (Jia et al 2017), they were found to be comparable. However, taking into consideration the large investment, complicated technology, and high energy consumption of the sintering process, the non-sintered ceramsites can be considered more advantageous.…”
Section: Water Absorptionmentioning
confidence: 80%
“…This increase in the compressive strength is also a major advantage of non-sintered ceramsites. Compared to the sintered ceramsite (Jia et al 2017), the compressive strength of non-sintered ceramsites was basically the same. The strength of some non--sintered ceramsites was lower than that of sintered ceramsites; however, the continued increase in the strength of non-sintered ceramsites after curing resulted in a compressive strength comparable to that of the sintered ceramics.…”
Section: Effect Of Raw Materials Distribution Ratio On Basic Properti...mentioning
confidence: 88%
“…Although sintered ceramsite have a macroscopic large pore structure but a relatively smooth microscopic surface, so there are almost no microporous and mesoporous structures on the surface of ceramsite [7,8]. Therefore, the specific surface area of the original sintered ceramsite is relatively small, resulting in poor adsorption capacity, far lower than that of other filter medias such as zeolite and activated carbon [9][10][11].…”
Section: Introductionmentioning
confidence: 99%